Plant Growth and Development in Relation to Phosphorus: A review - Amin FATHI; Jaber MEHDINIYA AFRA (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Agriculture, 2023)
Phosphorus (P) deficiency is a primal limiting factor for crop yields, particularly during the early developmental phase. This nutritious element plays a key role in several physiological mechanisms such as seed and fruit formation, respiration, photosynthesis, energy storage, and transfer, cell division, cell enlargement, and many other processes in the plant. Part of P applied to soil as fertilizer is could be into insoluble forms, rendering it unavailable to plants and causing environmental pollution. Therefore, increasing p absorption ability by plants appears to be critical for increasing agricultural productivity and decreasing pollution. Improving the crops P use efficiency (PUE) could be an effective method to increase P uptake. The maximum PUE is observed where nutrient supply via chemical fertilizer is the lowest level. This review discussed the significance of plant growth, yield quality, and PUE.